The Effect of Compensation on Work Quality With Work Motivation as An Intervening Variable in BPJS Employment Regional Office Of Northern Sumatra - Sinaga, Richard Alex Stepanus; B, Mesra (Neo Journal of economy and social humanities, 2024)
In this study, researchers wanted to see the direct and indirect effects between the Compensation variable as an independent variable and Work Motivation as an intervening variable and Work Quality as the dependent variable. This type of research uses quantitative, this research was conducted BPJS Employment Regional Office of North Sumatra. The population of this study was 80 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows Compensation has a positive and significant effect on work quality with an original sample value of 0.617 and P values of 0.000. Compensation has a positive and insignificant effect on work motivation with an original sample value of 0.099 and p values of 0.406. Work quality has a positive and significant effect on work motivation with an original sample value of 0.717 and p values of 0.000. Compensation has a positive and significant effect on work motivation through work quality indirectly with original sample results of 0.443 and p values of 0.000.